KAJIAN KAWASAN TERDEGRADASI DAN POLA PEMULIHAN EKOSISTEMDI KAWASAN SUAKA MARGA SATWA KO’MARA KABUPATEN TAKALAR - Sahruddin Sahruddin; Amir Tjoneng; Sudirman Numba (Percetakan Umi Toaha Makassar, 2018)
The study of degraded areas n the pattern of ecosystem restoration in the wildlife comma area of the Takalar district is a study that examines the location of degraded sites in wildlife reserves before ecosystem restoratioan activities in the area. This study aims to identify the extent of degraded sites, know the type of damage that occurs in a degraded location and determine the recovery pattern to be implemented. The area of degradation in the wildlife reserve in Takalar district is 298.84 ha, from the results of visual identification/image in 2016 then conducted direct measurement of wildlife sanctuary Ko’mara with an area of 122.65 ha. Determination of the type of damage to the degraded site is done by inventory of stand to determine the number of nature regeneration/seedlings, stable diameter 10 cm to 20 cm and stands ≥ 20 cm in diameter. The result of the stock inventory shows the type of damage to the degraded location in the Ko’mara wildlife reserve of Takalar district is moderately damaged with plant enrichment recovery pattern.